Building of Democratic Relationships from Progressive Autonomy and Empowerment as Means to Achieve the Participation Processes and Interlocution in Underage People within the Costa Rican Educative System - Naranjo Segura, Juan Carlos (2018)
The goal of this article is to foster discussion among theoretical principles, which would allowthe building of democratic relationships from the progressive autonomy and the empowermentas means to achieve the participation processes and interlocution, in underage people within theCosta Rican Educative System. Among the strongest ideas from the analysis rises the discussionabout the hypothesis of human needs, which nurtures arguments to rethink the building ofdemocratic relationship in underage people. Likewise, legal background for child’s rights setsthe bar for progressive autonomy and participation as backbone for social transformation. Fromthis point on, one of the key topics is to evidence the presence of certain conditions in theCosta Rican educational system, where each student could experience an authentic citizenship.